Dimensi kualitas tidur subjektif dan korelasinya dengan depresi pada pasien diabetes melitus tipe 2 - Ferdy Lainsamputty; Ivanna Junamel Manoppo (Jurnal Ilmu Keperawatan, 2022)
Diabetes mellitus (DM) is a metabolic disorder that causes 4-5 times higher mortality in Indonesia. DM patients have a greater risk of depression than individuals without this disease. This factor is one of the psychological problems that interfere patients’ sleep. This study aimed to determine the relationship between depression and sleep quality including its dimensions in patients with type 2 DM, as well as to identify the factors associated with it. This was a correlational study with cross-sectional design. The samples were 146 patients recruited using convenience sampling technique. Data were collected using the Beck Depression Inventory (BDI) and Pittsburgh Sleep Quality Index (PSQI) and analyzed using descriptive statistics, Mann-Whitney, Kruskal-Wallis, and Spearman Rank. The results showed that there was no significant relationship between depression and sleep quality (r = 0,08; p > 0.05). There was a significant and negative correlation between depression and the use of sleeping medicines (r = -0,19; p < 0.05). Type 2 DM patients who experienced mild depression, used more sleeping pills to get a better sleep.